TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) IN ACTION: A PORTRAYAL OF NOVICE TEACHER PRACTICE WITH ICT INTEGRATION INTO EFL CLASS - Afiatun, Tuty (2016)
Integrating information and communication technology (ICT) into teaching and learning activities requires teachers to possess not only technological knowledge, but also content and pedagogical knowledge. It means holding an attribute of being literate in ICT does not guarantee the teachers to be able to integrate ICT into instructional activities in a meaningful way. Responding to this issue, this study attempts to explore the novice English teachers' practice of ICT integration into EFL class viewed from the perspective of technological pedagogical and content knowledge (TPACK) framework. The main objectives of this study are to depict how the EFL novice teachers' perceived beliefs of their TPACK are reflected in their actual teaching practices, and to investigate the teachers' barriers in reaching the ideal practice of ICT integration into EFL class. Applying case study as the research approach, this study collected the needed data through the instruments of questionnaire, interview, and observation. Three English teachers from three different Junior High Schools in West Java participated this study. The findings of this study revealed that the novice teachers showed positive beliefs toward the practice of ICT integration into EFL class. The teachers' positive beliefs toward the practice of ICT integration into EFL class had led them to the consistent performance of their technological and content knowledge. However, the teachers started to show the discrepancy between their perceived beliefs and their actual teaching performances when dealing with pedagogical knowledge. Furthermore, this study also found that the school-level barriers played more dominant in hindering the teachers' optimal practice of ICT integration than the teacher-level barriers. Shortly, this study concluded the ideal practice of ICT integration into instructional activities was essentially a mutual symbiosis among the teachers' positive acceptance to teaching with technology, the teachers' well-established TPACK, and the school's supports. ;